Diseño de un sistema mecánico semiautomático para realizar ejercicios de fisioterapia de la rodilla - Cueva Julca, Freddy Joe (2018)
This work entitled "design of a semi-automatic mechanical system to perform physiotherapy exercises for the knee", it was developed using the genetic algorithms method, for the design of the four-bar mechanism. First the dimensions of the lower extremities were found for a person of 1.60 m, for which the book of anthropometric dimensions of the Latin American population and the model of the segments of the human body as a function of height were taken as a reference, based on This information was graphed in the GeoGebra software, and then simulated to obtain the 6 knee positions in flexion and extension in the four-bar mechanism. With the method of optimization of synthesis by genetic algorithm, applied to the generation of movement for six positions of a mechanism of four bars, it was achieved thanks to the Matlab program for it was generated a population of 1000 individuals randomly and encoded in the system binary after it is decoded based on the range of each variable of the links. Each individual created was evaluated through the objective function and for this the freudenstein equations had to be found. To evaluate the largest number of individuals, specific functions such as selection, crossing and mutation were used. This process was repeated for each generation. which allowed to find the lengths of the links (r1 = 41.960 cm), (r2 = 44.931 cm), (r3 = 41.960 cm), (r4 = 44.931 cm) of a mechanical system to perform physiotherapy of the knee. Also effort analysis was also made to determine the material of the links that is an ASTM A500 structural tube with a thickness of 2mm and diameter of ¾ ". Then for the power transmission was determined a speed ratio of 8 between the worm and gear in the design of the reducer to reduce the speed, with the calculations for the design of the reducer we obtained the input torque (3.6245 ) and the power input (3.085 ) that are necessary for motor selection.